Dissemination of Marketing Technology to Optimize and Accelerate the Marketing of Local Products in Muntuk Village - Iswanto Suwarno; Robbi Rahim; Mohammad Aljanabi; Omar Tanane; Erwin L. Rimban (Peneliti Teknologi Teknik Indonesia, 2022)
Muntuk Village is located in Dlingo District, Bantul Regency, Yogyakarta Special Region. The Muntuk Village area consists of 11 hamlets, namely Gunung Cilik Hamlet, Muntuk Hamlet, Sanggrahan I Hamlet, Sanggrahan II Hamlet, Banjarharjo I Hamlet, Banjarharjo II Hamlet, Tangkil Hamlet, Karangasem Hamlet, Seropan I Hamlet, Seropan II Hamlet, Seropan III Hamlet . the majority of the population of Dukuh Muntuk work as wood craftsmen (furniture) and bamboo (woven) craftsmen. However, there are also those who work as farmers and traders, but that is only a side job because their main job is wood and bamboo craftsmen. The main problem in wood and bamboo craftsmen is marketing. Therefore, the purpose of this community service is to introduce a marketing method that is more widespread and of course also cost-effective, namely by selling on an online media basis. Publication on social media, and through E-commerce media. Community service activities are assisted by students as well as entrepreneurship learning for students as entrepreneurship knowledge. The innovation being carried out is developing marketing through E-commerce based media which aims to expand the market segment of the skullcap industry.